(untitled) (Bangladesh Journal of Nuclear Medicine, 2024)
Cervical lymph node metastasis (CLNM) is frequently observed in differentiated thyroid carcinoma (DTC). After thyroidectomy, radioiodine (131I) treatment is advised to destroy any remaining thyroid tissue. It is still unknown how 131I therapy may affect the prognosis of DTC in CLNM patients. Our objectives were to examine the correlation between the ages of diagnosis and the results of 131I administration in individuals with DTC and CLNM and to examine the variables that might have an impact on clinical results. From 2004 to 2010, a total of 290 patients with PTC who received 131I administration following a near total or total thyroidectomy were recruited from the National Institute of Nuclear Medicine and Allied Sciences (NINMAS) and analyzed retrospectively. The selected patients were divided into two groups according to age: Group A (<18 years) and Group B (>18 years) with the presence of pre- or post-surgical and post-ablative lymph node metastases. The clinical outcomes are categorized as excellent response, indeterminate response and incomplete response. In Group A, out of 31, excellent responses had 16 (51.6%), indeterminate responses had 7 (22.6%), and incomplete responses had 8 (25.6%). In group B, out of 259, excellent responses had 99 (41.4%), indeterminate responses had 101 (42.3%), and incomplete responses had 39 (16.3%). Papillary thyroid cancer lymph node metastases are a potential predictor of prognosis. They are significant for the disease’s recurrence. Compared to adult patients, younger PTC patients with lymph node metastases exhibit a better response. Bangladesh J. Nuclear Med. 26(2): 133-139, 2023